UNDERSTANDING THE CONSTITUTIONAL DYNAMICS OF TRIBAL POLITY IN INDIA: THE STUDY OF LADAKH AND RAJASTHAN - Meena, Harsh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The term ‘Federalism’ refers to and deals with multiple aspects; it relates to administrative setup in the constitutional distribution of power in various layers of government. At the same time, it also works as a system to accommodate multiple identities in a plural administrative setup; it is fiscal and administrative, it can accommodate aspirations, and at the same time, it can adopt exclusivity. Comparative and cooperative can also be the dimension of federalism. As the word Federation is derived from the Latin word ‘foedus’, which means agreement or treaty, ironically, in modern plural democracies, it acts as the consensus builder and the reason for conflict, protest and movements. The paper will explore the various dimensions of federalism in India, particularly tribal polity. The tribes in India are not homogenous groups, and their heterogeneities can be seen in terms of their regional, culturally specific demands within the scope of federal arrangements in India. Politically and administratively, the Post-Independent India struggled to address the tribal aspirations. Even though administrative arrangements have been made to the constitution in the form of the Vth and VIth schedules, the tribal aspirations in the federal polity of India demand further accommodation and representation.